PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN POLITEKNIK LP3I JAKARTA - Purnomo, Djumat (JAB (Jurnal Akuntansi & Bisnis), 2018)
Employees are company assets that must be maintained and developed. Leadership in an organization needs to be based on vision and mission, goals and work programs have the needs of all parties and accommodate employees, and are able to provide encouragement as hard as employees work. Competencies need to be developed towards improving the company's financial reputation in general. One of the ways to improve employee competency is through employee development programs through education and training. The harmony of communication that exists between employees will greatly help improve the overall performance of the company, with the establishment of mutual understanding and joint work within the company.The Jakarta LP3I Polytechnic (PLJ) is one of the higher education institutions which since its inception sought to eradicate unemployment in Indonesia, especially in Jakarta. It is not an easy thing to prove it, but at least the LP3I Jakarta Polytechnic has begun to show that graduates are easy to work, even have worked before graduating D III. The success of their performance really needs to be studied, especially regarding leadership, competence and communication as reviewed in the previous paragraph.This study aims to determine respondents' responses to transformational leadership, competence and organizational communication among employees of the LP3I Jakarta Polytechnic and the influence of transformational leadership, competence and communication on the performance of LP3I Polytechnic employees in Jakarta.Â Keywords: transformational leadership, competence, communication and performance